The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1039/c6mb00231e
|View full text |Cite
|
Sign up to set email alerts
|

Small-molecule binding sites to explore protein–protein interactions in the cancer proteome

Abstract: The Cancer Genome Atlas (TCGA) offers an unprecedented opportunity to identify small-molecule binding sites on proteins with overexpressed mRNA levels that correlate with poor survival. Here, we analyze RNA-seq and clinical data for 10 tumor types to identify genes that are both overexpressed and correlate with patient survival. Protein products of these genes were scanned for binding sites that possess shape and physicochemical properties that can accommodate small-molecule probes or therapeutic agents (drugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 89 publications
1
14
0
Order By: Relevance
“…It was long believed that PPI interfaces are too large and not suitable for the binding of small molecules, which was one of the major reasons for slow progress in this field 2 , 3 . However, recent studies have shown that functional region in a PPI is small enough to be regulated by small molecules 1 , 3 , 4 . Almost all drug development using this approach has targeted “inhibiting” PPIs, where many of these drugs have entered various phases of clinical trials 2 , 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was long believed that PPI interfaces are too large and not suitable for the binding of small molecules, which was one of the major reasons for slow progress in this field 2 , 3 . However, recent studies have shown that functional region in a PPI is small enough to be regulated by small molecules 1 , 3 , 4 . Almost all drug development using this approach has targeted “inhibiting” PPIs, where many of these drugs have entered various phases of clinical trials 2 , 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Almost all drug development using this approach has targeted “inhibiting” PPIs, where many of these drugs have entered various phases of clinical trials 2 , 5 , 6 . Mechanistically, majority of these drugs bind one target protein and inhibit its ability to form a functional complex with its binding partner, thereby modulating its downstream signaling events 2 , 4 . Many small molecules have been developed that inhibit various PPIs including the Ras-SOS1 complex that produces anticancer effects by targeting Ras oncogene 4 , 7 ; small molecules LEDGINs were shown to inhibit LEDGF/p75-integrase binding 8 and inhibit HIV replication; Verteporfin was shown to inhibit YAO-TEAD complex with anticancer properties 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…To calculate druggability of the FERM F1 lobe and the specific pockets to target for virtual‐based drug discovery, we first started with the program SiteMap (Schrödinger), which utilizes a grid‐based searching algorithm to search for drug‐binding protein cavities and calculates the physiochemical properties of found cavities. This program is a useful tool when it comes to druggability determination of a variety of protein–protein interactions, including, but not limited to, PPIs on the cancer genome that drive cancer function (Halgren, 2009; Xu, Jalal, Sledge, & Meroueh, 2016). For these reasons, we chose to use SiteMap to determine the key druggability of the FERM F1 lobe.…”
Section: Resultsmentioning
confidence: 99%
“…To identify small molecules that bind to Ca V β at the protein-protein interaction interface, we resorted to virtual screening, focusing on the large binding cavity on Ca V β 3 . SiteMap (44) scoring of the cavity leads to a SiteScore of 1.01, suggesting that the pocket is highly druggable (45). Therefore, small molecules that bind to this pocket have the potential to exhibit in vivo efficacy similar to those of Food and Drug Administrationapproved drugs.…”
Section: Resultsmentioning
confidence: 99%